Thermal squeeze will exacerbate declines in New Zealand's endemic forest birds. (September 2019) - Walker, Susan; Monks, Adrian; Innes, John
Abstract: The effects of invasive species whose ranges are expanding in response to climate change have the potential to drive a new wave of extinctions in vulnerable species. We explore whether expansion of mammalian predators in New Zealand will lead to the thermal squeeze of a forest avifauna by investigating the mechanisms that have led to recent declines. Analysis of local occupancy across the three main islands between 1969–1979 and 1999–2004 shows that the ranges of predator-vulnerable endemic species are constrained by lowland forest loss and continued to contract to higher-elevation, colder parts of forested mountains. Species that are large, nest in tree cavities, and/or disperse poorly have undergone more rapid recent loss where temperatures are higher, consistent with higher and more constant predation in warmer forested sites being the principal mechanism of recent decline. Warming climate is likely to exacerbate local extinctions of predator-vulnerable species by reducing the extent of cool thermal refugia from continuously high predation pressure below the upper limit of forest. However, warming is unlikely to jeopardise small-bodied, non-cavity-nesting, mobile species, which have had stable or increasing populations in warm sites and largely deforested landscapes. New Zealand will share with Hawai'i the phenomenon of thermal squeeze of endemic forest bird species that is mediated by the changing range of an invasive species, rather than by native species themselves tracking their climatic niches. New Zealand will need to make substantial advances in large-scale predator management in warm forests to halt and reverse forest bird declines.